1995
DOI: 10.1002/hep.1840220225
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of N-acetylcysteine on hypothermic ischemia-reperfusion injury of rat liver

Abstract: We investigated whether intraportal injection of 150 mg/kg N-acetylcysteine (NAC) into rats reduced hepatic ischemia-reperfusion injury after 48 hours of cold storage and 2 hours of reperfusion. The organ was isolated and perfused to evaluate liver function. The control group received an intraportal injection of 5% dextrose. NAC increased L-cysteine concentrations 15 minutes after injection (1.29 +/- 0.11 mumol/g vs. 2.68 +/- 0.4 mumol/g, P < .05). However, neither treatment modified glutathione liver concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 30 publications
3
58
0
1
Order By: Relevance
“…Treated livers produced greater amounts of bile and had lower levels of enzymes when compared with controls. 3 Nakano et al 4 reported a direct protective effect on Kupffer cells and an enhancement of the concentration of cysteine within hepatocytes after an intraportal injection of NAC before liver harvesting in rats. Pretreatment with NAC helped maintain hepatic glutathione levels during warm ischemia, whereas when administered after ischemia and before reperfusion, NAC was effective in replenishing depleted glutathione stores in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Treated livers produced greater amounts of bile and had lower levels of enzymes when compared with controls. 3 Nakano et al 4 reported a direct protective effect on Kupffer cells and an enhancement of the concentration of cysteine within hepatocytes after an intraportal injection of NAC before liver harvesting in rats. Pretreatment with NAC helped maintain hepatic glutathione levels during warm ischemia, whereas when administered after ischemia and before reperfusion, NAC was effective in replenishing depleted glutathione stores in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the levels of lipid peroxidation products are lowered when GSH is added to organ storage fluids (Bryan et al, 1994). GSH plays an important role as a free radical scavenger (Nakano et al, 1995). In ischemic rats, hepatic GSH significantly decreased 5 and 24 h after reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In rat liver transplantation, NAC treatment reduced early phase reperfusion injury [5] and decreased leucocyte adherence to sinusoidal endothelium [23]. In a model of hypothermic I/R injury of the steatotic rat liver, NAC given before cold storage for 24 h diminished sinusoidal microcirculatory injury and lowered enzyme release after reperfusion [24].…”
Section: Discussionmentioning
confidence: 99%
“…The radical scavenging properties of N-acetylcysteine have been proven beneficial in several conditions involving oxidative damage, namely ischaemia/reperfusion injury in rat liver transplantation [5]. Consequently, NAC has been evaluated as a hepatoprotective agent in clinical OLT and has shown favourable results in a recent study [6], whereas other studies did not demonstrate clinical benefit [7,8].…”
Section: Introductionmentioning
confidence: 99%